Implementation of Restorative Justice for Criminal Offence Resolution in Indonesia Based on Police Regulation No. 8 of 2021 - Patuan Saur Andre Jeriko Sihombing; Surya Nita; Yopik Gani (Transpublika Publisher, 2025)
The implementation of restorative justice in the criminal justice system as regulated in Police Regulation No. 8 of 2021 aims to create a more humane case resolution by emphasizing victim recovery, perpetrator responsibility, and social balance. With this approach, the police can focus more on fair and balanced problem-solving so that justice is not merely about punishment, but also about restoring the social condition of society. This research uses a qualitative approach with a literature study method. The research results show that the implementation of restorative justice in Indonesia based on Police Regulation No. 8 of 2021 aims to resolve minor criminal cases through mediation between victims and perpetrators with certain conditions, namely general, material, formal, and specific requirements for certain criminal acts. This approach focuses on victim recovery and perpetrator responsibility, but is not applied to serious crimes such as terrorism and corruption. Although applied in cases such as domestic violence, assault by children, and minor traffic accidents, its implementation still faces obstacles related to legal understanding and resource limitations. The research implications show that the restorative justice approach based on Police Regulation No. 8 of 2021 reflects a paradigm shift in criminal law from a retributive model towards more humane substantive justice. This aligns with progressive and responsive legal theory, which positions law as a tool for social recovery and human rights protection beyond formal procedures.